Emissions from US-Mexico Border Crossings: Assessing Affected Populations in El Paso, Texas. (June 2018) - Ramani, Tara; Jaikumar, Rohit; Trueblood, Amber; Uwak, Inyang; Vallamsundar, Suriya; Johnson, Natalie; Zietsman, Josias
Abstract : Background: The US-Mexico border region has several major ports of entry, which serve as the gateway for large volumes of binational passenger and freight movement. Due to congestion and high wait times, vehicles are found to idle or "creep-idle" at border crossing locations, and these vehicles have been identified as a significant contributor to emissions in border areas. There are also concerns about the exposure of different groups of people - occupational exposures of truck drivers and workers in the border crossing facilities, commuters who cross the border, and residents who live and work near the border crossings. The El Paso region in Texas (across the border from Ciudad Juarez in Mexico) is home to some of the busiest border crossings in the US. The region is also in violation of federal ambient air quality standards. This study characterized the emissions impact of border crossings in El Paso to identify population groups, areas and neighborhoods potentially affected by emissions from the border crossing. Methods: A literature review was conducted on assessment of health impacts of traffic-related air pollution, with a focus on impacts at border crossings and similar near-road environments. This was followed by a qualitative assessment of the ports of entry in the El Paso region (some of which carry larger truck volumes and others that serve commuter traffic including pedestrians), and their surrounding areas, and the affected population groups (occupational exposures and well as local communities). Finally, a geographic information systems (GIS)-based multi-criteria assessment was conducted to screen and prioritize areas in El Paso that can be viewed as being most affected by border crossing. The variables considered included proximity to the border crossing, proximity to truck routes, prevailing winds, etc. These were overlaid with population and demographic data, including consideration of sensitive populations to identify "hot-spots" that were most affected by border crossing emissions. Results: This study provides insight into those affected by traffic-related air pollution generated by a border crossing, with a case study of the El Paso region. The results allow for the identification of neighborhoods or populations affected, who can be targeted for further exposure assessment studies including personal sampling studies, or for health interventions. Conclusions: The study approach provides a systematic GIS-based approach for the screening of affected populations in a unique context (border crossings). The findings are relevant to address emissions exposure, health impacts, and environmental justice issues in border regions.